Ethics Political Communication Using Gayo Cultural System Approach (edet gayo) - Basri, Hasan; Efendi, Muhsin (Jurnal Politik Indonesia: Indonesian Political Science Review, 2021)
Ethics political communication used in the order in the government presented opinion or advice necessary keep a message manners according to customs culture gayo have separate ethics had meaning very important. Ethics political communication by the government to the society will affect any good; on the contrary, political communication also to the government will feed into aspects in improving the good order. Ethics political communication community groups as expressing an opinion society organizations politely and mannered use gayo culture and so is government response in accommodating the aspirations of the organizations. District of Aceh central gayo occupying an integral part of Indonesia. Those who have the character and values of the specific customs and culture of Indonesian society in general. The gayo customs and cultural values make the values of the Gayo customary philosophy in everyday life. The system of cultural values of the gayo community at events contains knowledge, beliefs, values, religion, norms, rules, and laws that become a reference for behavior in community life, the philosophical values of the gayo community, cannot be separated from the customs/culture of the gayo community as;  Genap mupakat (democracy), amanat (integrity), tertip (orderly rules), alang tulung beret bantu (mutual help), gemasih (affection), setie (loyal), bersikekemelen (competing), dan mutentu (effective). Courteousness in conveying aspirations and opinions to the government and the government to the community must have politeness ethics in political communication to avoid inconsistencies and insecurity between the people and the government in Central Aceh